Prinsip-Prinsip Manajemen Pendidikan Islam - Nur Wahib (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2018)
Islamic Religious Education with various paths, levels, and forms that exist such as in the formal education path there are basic education levels in the form of Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MTs), secondary education levels are in the form of Madrasah Alyah (MA) and Madrasah Aliyah Vocational Education (MAK), and at the higher education level there are so many Islamic Religious Universities (PTAI) with various forms, some of which are in the form of academies, Colleges, Institutes, and Universities. In non-formal education channels such as Playgroups, Child Care Parks (TPA), Ta'lim Council, Islamic Boarding Schools and Madrasah Diniyah. Informal Education Paths such as education held within the family or education organized by the environment. All of this needs the best possible management or management, because if not only the negative image of Islamic education that exists in society will remain attached and difficult to remove, maybe even Islamic education whose rights will be destroyed by falsehood that is managed and neatly arranged in the community. around him, as stated by Ali bin Abi Talib: "truth that is not neatly organized will be destroyed by well-organized falsehood".